PERTANGGUNGJAWABAN PIDANA DAN PERLINDUNGAN HUKUM BAGI PELAKU TINDAK PIDANA DENGAN GANGGUAN KEJIWAAN - Tapowolo, Wilhelmina Maria Peni; Medan, Karolus K.; Dima, Adrianus Djara (The Juris, 2025)
Crimes committed by Persons with Mental Disorders (ODGJ) are a complex phenomenon that demands special attention from the aspects of criminal law and human rights protection. When the perpetrator of a criminal act suffers from a mental disorder, criminal liability cannot be imposed in accordance with the provisions of Article 44 of the Criminal Code (KUHP). The legal protection provided to perpetrators of criminal acts with mental disorders has also not been implemented properly in accordance with the provisions of the applicable law. Based on this, the problem is formulated: (1) can a person with a mental disorder be held accountable for the act of murder committed? (2) What is the legal protection for people who commit the crime of murder who are classified as having a mental disorder? This study uses a combination of normative legal research methods and empirical legal research methods. This research was conducted in Wulanggitang District, East Flores Regency. The data is analyzed qualitatively. Based on the results of the research, the murder case carried out by FTA, a person with mental disorders (ODGJ), shows that the perpetrator cannot be criminally accounted for according to Article 44 of the Criminal Code because the mental disorder he experienced makes him unable to understand and control his actions. The subjective element of error and legal responsibility is not met, even though the objective element of causality of death has occurred. Therefore, the legal process ended with the issuance of an Investigation Termination Order (SP3). However, legal protection for ODGJ such as FTA has not been implemented properly. The perpetrator was subjected to attachment and neglect by the family, which is contrary to the provisions of the law and fundamental rights guaranteed by the 1945 Constitution and related laws.